Multipath routing protocol based on cross-layer approach for MANET - Allahham, Alaa Azmi; Mohammed, Muamer N.; Kadhim, Nassir Sallom (International Association of Online Engineering, 2017)
Mobile Ad-hoc Networks (MANETs) involved in many applications, whether smart or traditional and for both civilian and military uses, and that because of their special features, where it does not depend on any infrastructure during its working, as well as the nodes in MANETs have a freedom of movement with the ability to self-configure, in addition, to working as a router or client at the same time. Moreover, MANETs considered as an infrastructure less network, so the cost of this type of networks is less in comparison to other traditional networks. On the other hand, the routing considered one of most important challenges in MANETs due to the perpetual motion and randomness of the nodes that can causing a continuous change of the network topology and thus to all paths between nodes, where finding valid paths between the nodes is the core task of routing protocols. Recently, it has been argued that the traditional layered architecture is ineffective to deal with receiving signal strength related problems. In an effort to improve the performance of MANETs, there has been increased in protocols that rely on cross-layer interaction between different layers. In this paper, a Cross-layer design among Network, MAC and Physical layers based on Threshold Multipath Routing Protocol (CTMRP) is proposed. The CTMRP is designed for decision maker based on threshold value of average paths signal for efficient transmission of the Text, image, audio and video as well as sending the data via multiple paths, which mitigate the negatives effects causes from forcing the nodes to send the data via single. The Route Discovery Delay, Number of RREQ Messages, Number of RREP Messages, End-to-End Delay, Packet Delivery Ratio (PDR), and Throughput were selected as the main performance evaluation metrics. The results show that the proposed algorithm has better performance and lead to increase stability of transmission link.